The Effects of Using Digitalization, Work Life Balance and Work Engagement on Employee Performance Through Job Satisfaction at PT Waskita Karya Infrastruktur - Dewi, Cahya Tri Tungga; Krisnadi, Herry (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
Employee performance is a key factor in a company's success. This study aims to analyze the factors that affect employee performance in PT Waskita Karya Infrastruktur companies in Jakarta. The quantitative research approach was used with the partial least (SEM-AMOS-22) method to analyze data collected through questionnaire techniques as primary data collection techniques. The sample consists of 128 respondents. The results show that digitalization has a positive and significant influence on employee performance. The application of digital technology in business processes and company operations can increase employee efficiency and productivity as well as accelerate access to the information needed to carry out their duties. Based on the results of the study, it can be concluded that digitalization, work life balance, and work engagement have a positive and significant influence on employee performance through job satisfaction.